Household Consumption and the Housing Net Worth Channel in Ireland - Cronin, David; McQuinn, Kieran (The Economic and Social Review, 2023)
The performance of the Irish economy varied considerably over the period 2002-2019, with a credit-led boom up to 2007 being followed by a sharp fall in economic activity and house prices in the following five years and then a recovery in both output and the housing market. This provides a valuable sample for investigating the relevance of the housing net worth channel to consumption developments. The evidence presented here indicates the channel being active in Ireland during the 2007-2012 downturn with a fall in house prices being associated with a decline in consumption. It does not have an impact outside that downturn. Accordingly, the results add to the international evidence of how an accumulation of household debt and a downturn in house prices has an adverse impact on consumption.